Diseños para productos textiles mediante la síntesis formal de la indumentaria de la mama negra, en la fiesta de la virgen de la merced en la ciudad de Latacunga, provincia de Cotopaxi - Chicaiza Morocho, Diego Fernando (2017)
The use of textile products as a mass media has become an innovative idea at the moment of offering a product or service, for that reason it has considered the proposal of this research, the creation designing for textile products through a formal synthesis of “Mama Negra” clothing at the party of la Virgen de la Merced in Latacunga, Cotopaxi province which has the purpose to make known the symbols that are used in “Mama Negra” clothing, using as the initiative the basic designing to remove the symbols and create modules that they are applicable in textile products. In the process of this research will be applied different research techniques with the purpose of gathering information and data about the problem there is in the media this popular festival in order to find a feasible solution. The designing will be applied in different textile products because they have advantages at the moment of publishing or promote a product or service, consequently the general public visualize and consume what they call the attention….